(untitled) (Research, Society and Development, 2022)
Celebrating the centenary of calcium hydroxide (CH), the aim of this study was to analyze the 100 most-cited papers on this biomaterial. The bibliometric analysis was conducted in the Web of Science Core Collection (WoS-CC) database. Title, authorship information, study design, year, journal, number of citations, CH use, and fields of Dentistry were extracted. The number of citations in the WoS-CC, Scopus, and Google Scholar databases was cross-matched with the Spearman correlation. From the 1,596 papers identified, a list was compiled with the 100 most-cited papers. The number of citations in WoS-CC ranged from 78 to 384 (mean: 131.4). The main CH uses were: intracanal dressing (61%), and pulp protection (29%). The fields of Dentistry with most studies on CH were Endodontics (62%) and Operative Dentistry (30%). The most frequent study design was laboratory studies (44%). Three hundred and thirty-five authors from 29 countries were identified. The United States of America (USA) was the leading country with 23 articles. Dag Ørstavik was the author with the most papers and citations (9 papers; 1,118 citations). Most papers were published between 1991 and 2015 and in the Journal of Endodontics (38%). A very strong positive correlation was observed among the number of citations in the databases. The 100 most-cited papers were published mainly by European journals or from USA, with laboratory and multifaceted interventional designs. The present study celebrated the centenary of CH, highlighting the role and importance of this biomaterial in Dentistry.